Endoscopic Ultrasound-Guided Biliary Drainage for Unresectable Hilar Malignant Biliary Obstruction - Yousuke Nakai; Hirofumi Kogure; Hiroyuki Isayama; Kazuhiko Koike (Korean Society of Gastrointestinal Endoscopy, 2019)
Endoscopic transpapillary biliary drainage is the current standard of care for unresectable hilar malignant biliary obstruction (MBO) and bilateral metal stent placement is shown to have longer patency. However, technical and clinical failure is possible and percutaneous transhepatic biliary drainage (PTBD) is sometimes necessary. Endoscopic ultrasound-guided biliary drainage (EUS-BD) is increasingly being reported as an alternative rescue procedure to PTBD. EUS-BD has a potential advantage of not traversing the biliary stricture and internal drainage can be completed in a single session. Some approaches to bilateral biliary drainage for hilar MBO under EUS-guidance include a bridging method, hepaticoduodenostomy, and a combination of EUS-BD and transpapillary biliary drainage. The aim of this review is to summarize data on EUS-BD for hilar MBO and to clarify its advantages over the conventional approaches such as endoscopic transpapillary biliary drainage and PTBD.